2022
DOI: 10.1126/science.abk3126
|View full text |Cite
|
Sign up to set email alerts
|

8000-year doubling of Midwestern forest biomass driven by population- and biome-scale processes

Abstract: Changes in woody biomass over centuries to millennia are poorly known, leaving unclear the magnitude of terrestrial carbon fluxes before industrial-era disturbance. Here, we statistically reconstructed changes in woody biomass across the upper Midwestern region of the United States over the past 10,000 years using a Bayesian model calibrated to preindustrial forest biomass estimates and fossil pollen records. After an initial postglacial decline, woody biomass nearly doubled during the past 8000 years, sequest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 60 publications
1
3
0
Order By: Relevance
“…Although we did not address legacy effects empirically in this study, the observed lower C stocks in the early 20th century in the East, as well as the rejuvenation and strong stock regrowth in this region compared to the other regions and later decades, point to the importance of past uses of forests for contemporary observed forest developments. This argumentation is in line with historical literature (e.g., MacCleery, 1993;Maxwell, 1973) and previous studies on past U.S. land use and forest change (e.g., Houghton, 1999;Raiho et al, 2022).…”
Section: Discussionsupporting
confidence: 90%
“…Although we did not address legacy effects empirically in this study, the observed lower C stocks in the early 20th century in the East, as well as the rejuvenation and strong stock regrowth in this region compared to the other regions and later decades, point to the importance of past uses of forests for contemporary observed forest developments. This argumentation is in line with historical literature (e.g., MacCleery, 1993;Maxwell, 1973) and previous studies on past U.S. land use and forest change (e.g., Houghton, 1999;Raiho et al, 2022).…”
Section: Discussionsupporting
confidence: 90%
“…However, accounting for durability concerns is challenging, as the risk to existing carbon stores depends on how forests respond to climate change. Paleoecological records show that ecosystems can reorganize in response to climate-driven shifts (Iglesias and Whitlock, 2020;Raiho et al, 2022), but rapid environmental changes may hinder successful reorganization, leading to widespread mortality as many forests approach ecological tipping points (McDowell et al, 2020;Forzieri et al, 2022;Reyer et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Every place on Earth has a dynamic ecological trajectory based on temperature, rainfall, soils, natural disturbances, and other conditions. In the Northeast and Upper Great Lakes regions of the United States the predominant ecological trajectory of the landscape in the absence of intensive human activity is toward "old-growth" forests: a resilient, diverse, carbon-dense, and self-sustaining "shifting mosaic" of tree ages, microhabitats, and native species above and below ground (Pelley, 2009;Raiho et al, 2022).…”
Section: History Of Forest Development and Disturbancementioning
confidence: 99%